PENERAPAN MODEL BERPASANGAN UNTUK MENINGKATKAN HASIL BELAJAR PASSING BAWAH BOLA VOLI SISWA KELAS V SDN BERTINGKAT KABUPATEN GOWA - Karim, Achmad (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is a classroom action research conducted in two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. This study aims to improve the learning outcomes of underhand passing in volleyball for students at SDN Bertingkat Gowa Regency using the pair model. The subjects in this study were 16 students at SDN Bertingkat Gowa Regency. Based on the research conducted, it can be concluded that the application of the pair model can improve the learning outcomes of underhand passing in volleyball for students at SDN Bertingkat Gowa Regency. The results of the data analysis indicate a significant increase in the learning outcomes of underhand passing in volleyball for students at SDN Bertingkat Gowa Regency. In the first cycle, the passing percentage for students at SDN Bertingkat Gowa Regency was 62.50%, and increased to 93.75% in the second cycle.